2010
DOI: 10.1002/ijc.25067
|View full text |Cite
|
Sign up to set email alerts
|

Secondary malignant neoplasms after Wilms tumor: An international collaborative study

Abstract: A combined cohort of 8,884 North American, 2,893 British and 1,574 Nordic subjects with Wilms tumor (WT) diagnosed before 15 years of age during 1960-2004 was established to determine the risk of secondary malignant neoplasms (SMN). After 169,641 person-years (PY) of observation through 2005, 174 solid tumors (exclusive of basal cell carcinomas) and 28 leukemias were ascertained in 195 subjects. Median survival time after a solid SMN diagnosis 5 years or more from WT was 11 years; it was 10 months for all leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 49 publications
8
67
1
2
Order By: Relevance
“…This finding may reflect the different cancerogenic mechanisms that lead to solid tumors or leukemia, following radiotherapy and chemotherapy, respectively. 11 In our study, we observed an increased risk of digestive organs, bones and thyroid cancer but also brain cancer, and we did not observe an increased leukemia risk. Given the high incidence of secondary brain cancer, and because we could not distinguish between different types of renal tumors, we checked the latency between the renal and the secondary brain tumors to investigate the possibility of rhabdoid tumors' brain metastases.…”
Section: Epidemiologycontrasting
confidence: 38%
See 4 more Smart Citations
“…This finding may reflect the different cancerogenic mechanisms that lead to solid tumors or leukemia, following radiotherapy and chemotherapy, respectively. 11 In our study, we observed an increased risk of digestive organs, bones and thyroid cancer but also brain cancer, and we did not observe an increased leukemia risk. Given the high incidence of secondary brain cancer, and because we could not distinguish between different types of renal tumors, we checked the latency between the renal and the secondary brain tumors to investigate the possibility of rhabdoid tumors' brain metastases.…”
Section: Epidemiologycontrasting
confidence: 38%
“…30 A recent study that combined three cohorts of children with Wilms tumor for a total of 13,351 subjects followed for a median time of 11.6 years, observed the occurrence of 174 solid tumors, among which the most frequent were tumors of digestive organs, bones, breast, thyroid and 28 leukemias. 11 This study partially overlaps with ours, because one of the three cohorts consisted of 1,574 cases recorded in the cancer registries of Norway, Denmark, Iceland, Sweden and Finland from 1960 up to 2004. The study found that for solid tumors, the risk increased with age and time since Wilms' tumor diagnosis but decreased with calendar period of diagnosis.…”
Section: Epidemiologymentioning
confidence: 73%
See 3 more Smart Citations